Pengembangan Media Pembelajaran Passing Bola Basket menggunakan Kartu Tugas pada Pembelajaran Penjasorkes bagi Siswa Kelas VIII UPT SMP Negeri 1 Alla Kabupaten Enrekang - Suhardi Suhardi (CV. Syntax Corporation Indonesia, 2022)
Physical education, sports and health are one of them, it is necessary to create a learning atmosphere and learning process, so that students can actively develop their potential, have spirituality, religion, self-control, personality and intelligence, noble character and skills needed. by himself, society, the state and the world community. Physical education has a very close relationship with sports learning, sports learning is one form of learning whose aim is to improve the quality of physical movement. This study aims to develop and produce products in the form of media for passing basketball for junior high school students in learning physical education, sports and health to overcome students' difficulties in understanding basic basketball passing techniques. From the results of the study obtained expert evaluation data, namely, Physical Education experts 78.33% (good), learning experts I 91.66% (very good), learning experts II 81.66% (good), small group trials 89% (good ), and field trials 92.32% (very good). Then the increase in the average pulse rate of students after learning increased by 63.76% and increased maximum pulse rate by 70%. From the existing data, it can be concluded that the passing learning model Basketball using an assignment card can be used for students of UPT SMP Negeri 1 Alla, Enrekang district.